Focus and impact on environmental health and biodiversity - CGIAR Initiative on NEXUS Gains (International Water Management Institute, 2024)
A NEXUS Gains impact area brief shares how the Initiative’s five work packages aim to increase productivity in food systems while improving environmental systems, including biodiversity.